TWO TYPES OF PERSONALITY AMONG OFFENDERS: THE DIFFERENCES IN PSYCHOPATHY, AGGRESSIVENESS AND CRIMINAL ACTS - Dinić, Bojana; Barna, Jelena; Trifunović, Biljana; Angelovski, Aleksandra; Sadiković, Selka (Primenjena psihologija, 2016)
The aim of this research was to examine classification of offenders based on personality traits. On a sample of 166 male inmates, convicted of violent offenses, several instruments were applied: a short version of the Big Five plus two (BF+2-70), the Psychopathy Assessment Questionnaire (PAQ), and the Aggressiveness questionnaire AVDH. Results of the analysis of latent profiles showed that two classes could be identified based on BF+2-70 scores – a class of aggressive and a class of emotionally stable offenders. Thereby, the main differences between the classes were primarily in a tendency toward reactive aggression and neuroticism, which were more common in the offenders from the aggressive class. When controlling for age, the classes differed in anger and dominance, in the domain of aggressiveness, and in interpersonal style in the domain of psychopathy, although differences in interpersonal style were of small effect size. The differences were in favor of the aggressive class. Furthermore, offenders in the aggressive class were more frequently convicted of violence against property, whereas both classes had the same number of offenders convicted of murder. Identification of two classes of offenders has theoretical and practical implications for subtyping of offenders and understanding the tendency towards certain violent crimes.